Composição química e qualidade fisiológica de sementes de girassol de plantas submetidas à competição intraespecífica - Alves, Fernanda Vieira (2010)
The great number of seeds in the sunflower head and the temporal distribution of its maturation cause the competition between whorls because of nutritional resources and, consequently, differences in the seed chemical composition from the head regions. As the competition among plants in the sowing line can influence seeds nutrient drainage, this work aimed at evaluating both the chemical composition and the physiologic quality of sunflower plants seed coming from different regions of the sunflower head and plants stemming from high, low vigor seeds that partook of intra-specific competition. Three experiments constituted dealing with seeds coming from one third of the head (peripheral, median and central) were carried out. The experimental design was in randomized blocks with four repetitions, each experiment treatment being distributed on a subdivided plot. In the plots, it was evaluated five proportions of high-vigor seeds placed in the sowing line as it follows: 0,75 (3A:1B); 0,67 (2A:1B); 0,50 (1A:1B); 0,33 (1A:2B), and 0,25 (1A:3B). In the subplot, it was evaluated plants stemming from seeds of high and low vigor and two additional treatments (all plants coming from seeds of high or low vigor, 1A:1A and 1B:1B, respectively). After that, an analysis relating vigor proportions to the head thirds was made. It was evaluated the percentage of proteins, lipids, total carbohydrates, ashes, moisture degree, the weight of a thousand seeds, emergency measures (its initial, ending, and middle times, emergence and average velocity, uncertainty, synchronicity, time variation coefficient and emergency) obtained through emergency test in the sand. It concludes that: a) the proportion of vigor of the seeds in the sowing line interfere in performance of the plants and in seed quality resultant, being that the plants coming of seeds put in major proportion in the line, independently of the vigor have major competitiveness; b) the chemical composition of the sunflower seeds ranged with the position of the seeds in the head. Higher content of carbohydrates and weight of thousand seed were observed in the peripheral third, while the higher content of protein and lipids were obtained of the seeds in the middle third; c) the position of the seed in the head interfered in the variables of germination. Although sunflower head s third peripheral seeds showed a higher emergency ignition in the sand, it showed a lower final time and time variation coefficient, besides being having a higher emergency homogeneity and synchrony. The middle third seeds, on the other hand, showed low emergency homogeneity and synchrony, being more distributed in time.